Merkel cell carcinoma. Issue 4 (16th June 2021) - Mistry, K.; Levell, N. J.; Craig, P.; Steven, N. M.; Venables, Z. C.
Abstract: Merkel cell carcinoma (MCC) is a rare neuroendocrine carcinoma. The cellular origin of MCC may include Merkel cell precursors. The incidence of MCC has increased significantly however trends may have been confounded by evolving diagnostic criteria. The two key aetiologies of MCC are ultraviolet radiation and Merkel cell polyoma virus (MCPyV). Both have unique mechanisms of carcinogenesis. MCC presents non‐specifically as a rapidly growing, red‐to‐violet nodule on sun‐exposed areas. Diagnostic accuracy has improved through immunohistochemical markers such as CK‐20. Lymph nodes should be evaluated in MCC through examination and sentinel biopsy. USS, CT, MRI and CT‐PET may be useful in staging. Management depends on tumour location, stage and comorbidities. MCPyV status may guide treatment strategy in the future. Treatment for the primary MCC is commonly wide local excision followed by radiotherapy, guided by anatomical constraints. There is uncertainty about surgical margins. Treatments for nodal disease have not been determined through trials. They include nodal dissection or radiotherapy for clinically or radiologically apparent disease, and adjuvant nodal irradiation for negative nodes, microscopic disease or following nodal dissection for definite disease. Patients with loco‐regional advanced inoperable disease should be considered for combination therapy including chemotherapy, radiotherapy, surgery and immunotherapy. Systemic therapy for advanced disease includes immune checkpoint inhibitors targeting the PD‐1/PD‐L1 pathway. Avelumab can improve survival in metastatic MCC. Immunotherapy may result in longer disease control. Various other immunotherapeutic and molecular agents are undergoing trials. MCC continues to have a high mortality characterized by high recurrence and early metastases. Abstract : Merkel cell carcinoma (MCC) is a rare neuroendocrine carcinoma. MCC continues to have a high mortality characterised by high recurrence and early metastases. Diagnostic accuracy has improved through immunohistochemical markers such as CK‐20.